Familiarity of Physicians and Nurses with Different Aspects of Oxygen Therapy; a Brief Report - Goharani, Reza; Miri, MirMohammad; Kouchek, Mehran; Sistanizad, Mohammad (Archives of Academic Emergency Medicine, 2017)
Introduction:Â Oxygen is a drug and physician and nurses should be familiar with the effects and potential risks of oxygen therapy. The current study aimed to assess familiarity of physicians and nurses with various aspects of oxygen therapy. Method:Â In this cross sectional study, the familiarity of physicians and nurses with various aspects of oxygen therapy in a teaching hospital was evaluated using a validated questionnaire. The collected data were analyzed using SPSS 21 software. Results:Â 57 physicians and 79 nurses returned the completed questionnaire (response rate 97.1%). Mean clinical work experience of participants was 6.9Â±5.7 (1â€“15) years. 98.2% of physicians believed that oxygen therapy can be associated with risk and should be recorded in the patient’s medical file. These measures were 92.4% and 98.2% for nurses. 38 (27.9%) participants correctly pointed out the reasons for oxygen therapy. Regarding necessary measurements and monitoring for oxygen therapy, 49 (86%) physicians and 65 (82.3%) nurses chose the correct answer. In addition, regarding necessity of blood gas analysis during oxygen therapy, 44 (77.2%) physicians and 55 (69.6%) nurses chose the correct answer. Conclusion:Â The findings showed that the familiarity level of participants with some aspects of O2Â therapy such as its indications, necessary measurements and monitoring during therapy, and identifying delivery devices was fair to weak (<80%).